Emergency imaging in paediatric oncology: a pictorial review - Trevor Gaunt (Insights into Imaging, 2019)
Abstract Despite the decline in mortality rates over the last 20 years, cancer remains one of the leading causes of death in children worldwide. Early recognition and treatment for acute oncological emergencies are vital in preventing mortality and poor outcomes, such as irreversible end-organ damage and a compromised quality of life. Imaging plays a pivotal and adjunctive role to clinical examination, and a high level of interpretative acumen by the radiologist can make the difference between life and death. In contrast to adults, the most accessible cross-sectional imaging tool in children typically involves ultrasound. The excellent soft tissue differentiation allows for careful delineation of malignant masses and along with colour Doppler imaging, thromboses and large haematomas can be easily identified. Neurological imaging, particularly in older children is an exception. Here, computed tomography (CT) is required for acute intracranial pathologies, with magnetic resonance imaging (MRI) providing more definitive results later. This review is divided into a ‘body systems’ format covering a range of pathologies including neurological complications (brainstem herniation, hydrocephalus, spinal cord compression), thoracic complications (airway obstruction, superior vena cava syndrome, cardiac tamponade), intra-abdominal complications (bowel obstruction and perforation, hydronephrosis, abdominal compartment syndrome) and haematological-related emergencies (thrombosis, infection, massive haemorrhage). Within each subsection, we highlight pertinent clinical and imaging considerations. The overall objective of this pictorial review is to illustrate how primary childhood malignancies may present with life-threatening complications, and emphasise the need for imminent patient management.